“Measuring Silences” in the Translation of Awa Thiam's La Parole aux Négresses - Amanda Walker Johnson (Studies in 20th & 21st Century Literature, 2023)
An overlooked, yet significant text in the genealogy of intersectionality and Black feminist theory is Awa Thiam’s 1978 text La Parole aux Négresses. This paper examines the ways that the English translation, Speak Out, Black Sisters: Feminism and Oppression in Black Africa,though widening the audience for Thiam’s work, engages in various practices of erasure that undermine Thiam’s academic authority, theoretical contributions, activist insights, and ultimately, her own voice. Namely, I contend that these practices, which scholars have linked to receptions and English translations of Black Francophone texts in particular, include de-formalization, domestication, de-philosophizing, untracing, and invisibilisation. I seek not just to focus on the “negative” aspect of these silences, but also to enact a partial restitution of Thiam’s insights from the original French text. Further, re-engaging with her text, contributions, and insights calls for more reflexivity around the politics of translation, English language hegemony, and recognition of African feminist scholarship.
Keywords: Black Feminism; Politics of Translation; Anticolonialism; Intersectionality; Awa Thiam